Acetate Improves the Killing of Streptococcus pneumoniae by Alveolar Macrophages via NLRP3 Inflammasome and Glycolysis-HIF-1α Axis - Machado, Marina Gomes; Patente, Thiago Andrade; Rouillé, Yves; Heumel, Severine; Melo, Eliza Mathias; Deruyter, Lucie; Pourcet, Benoit; Sencio, Valentin; Teixeira, Mauro Martins; Trottein, François (Frontiers in Immunology, 2022)
Short-chain fatty acids (SCFAs) are metabolites produced mainly by the gut microbiota with a known role in immune regulation. Acetate, the major SCFA, is described to disseminate to distal organs such as lungs where it can arm sentinel cells, including alveolar macrophages, to fight against bacterial intruders. In the current study, we explored mechanisms through which acetate boosts macrophages to enhance their bactericidal activity. RNA sequencing analyses show that acetate triggers a transcriptomic program in macrophages evoking changes in metabolic process and immune effector outputs, including nitric oxide (NO) production. In addition, acetate enhances the killing activity of macrophages towards Streptococcus pneumoniae in an NO-dependent manner. Mechanistically, acetate improves IL-1β production by bacteria-conditioned macrophages and the latter acts in an autocrine manner to promote NO production. Strikingly, acetate-triggered IL-1β production was neither dependent of its cell surface receptor free-fatty acid receptor 2, nor of the enzymes responsible for its metabolism, namely acetyl-CoA synthetases 1 and 2. We found that IL-1β production by acetate relies on NLRP3 inflammasome and activation of HIF-1α, the latter being triggered by enhanced glycolysis. In conclusion, we unravel a new mechanism through which acetate reinforces the bactericidal activity of alveolar macrophages.